National Education Policy 2020 : Imagining Digital Technologies as a Resource to Achieve Educational Aims - Kasinathan, Gurumurthy (Voices of Teachers and Teacher Educators, 2021)
The National Education Policy, 2020 (NEP) asserts that education is fundamental for achieving full human potential, and for the development of an equitable and just society. Clearly, digital technologies are impacting our lives in all aspects - social, political, economic. The effectives of such impact in education would need to be seen against the extent to which its use can support in the achievement of educational aims. The NEP rightly visualizes that digital technologies can play a big role in creating, revising, curating, adapting and publishing of curricular resources in multiple languages spoken in the country, to create a rich learning environment in all courses at all levels, including through translation. While the NEP doesemphasize the need for digital technologies to support teacher professional development, it sees it largely in terms of building skills of teacher to become ‘users’. Yet critical perspectives on technology are most relevant, specially in the context of dangers to the aims of education through privatization and commercialization of education, hence teacher development needs to enable teachers to become creators, visualizers, designers of digital technologies to their contexts, and be restricted to using products developed by business entities. The NEP rightly points to the dangers of implementing unproven digital technologies (which has led to a very large number of failed projects), and recommends a process to screen digital methods. The dangers from the ‘new guy’ - “artificial intelligence” are not adequately emphasized in the NEP. Uncritical adoption of the latest craze of ‘personalized learning’ can derail the basic premise of education as social constructivism, and its purpose as social transformation.